1997
DOI: 10.1007/s002040050401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subchronic 2,3,7,8-tetrachlorodibenzo- p -dioxin exposure on immune system and target gene responses in mice: calculation of benchmark doses for CYP1A1 and CYP1A2 related enzyme activities

Abstract: The dose-effect relationships were analysed for several noncarcinogenic endpoints, such as immunological and biochemical responses at subchronic, low dose exposure of female C57BL/6 mice to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). The animals were treated i.p. with TCDD according to the initial- and maintenance-dose principal for a period of 135 days. The initial doses were 1, 10 and 100 ng TCDD/kg, the weekly maintenance doses were 0.2, 2 and 20 ng TCDD/kg, respectively. At days 23, 79 and 135 of TCDD/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…The AhR has been shown to play important roles in regulating the expression of several cytokines. For example, exposure of rats to TCDD led to up-regulation of IL-1␤ and TNF-␣ in the liver (57,58). Interestingly, although TCDD suppressed the production of IFN-␥ by mediastinal lymph node cells, there was a 10-fold increase in the IFN-␥ level in the lungs of TCDD-treated mice (59).…”
Section: Discussionmentioning
confidence: 99%
“…The AhR has been shown to play important roles in regulating the expression of several cytokines. For example, exposure of rats to TCDD led to up-regulation of IL-1␤ and TNF-␣ in the liver (57,58). Interestingly, although TCDD suppressed the production of IFN-␥ by mediastinal lymph node cells, there was a 10-fold increase in the IFN-␥ level in the lungs of TCDD-treated mice (59).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of the enzymatic activity of CYP1A1, frequently measured as ethoxyresoru® n-O-deethylase (EROD), or aryl hydrocarbon hydroxylas e (AHH), parallels that of the mRNA. Vogel et al (1997) observed signi® cant induction of EROD activity at a dose of~0.3ng/kg/ day. Kohn et al (1993) observed induction of CYP1A1 mRNA at 0.1 ng/kg/day in rats.…”
mentioning
confidence: 84%
“…Induction of CYP1A2 mRNA and protein occurs at similar doses to that of CYP1A1. Vogel et al (1997) demonstrat ed induction of CYP1A2 mRNA at a dose of~0.3 ng/kg/day, with a NOEL of~0.03 ng/kg/day. Measurements of the activity of this enzyme often involve the hydroxylation of acetanilide (ACOH) or the demethylation of methoxyreso ru® n (MROD).…”
mentioning
confidence: 95%
See 2 more Smart Citations